2020
DOI: 10.24875/gmm.20005607
|View full text |Cite
|
Sign up to set email alerts
|

Riesgo de resangrado en hemorragia digestiva alta según la escala de Glasgow-Blatchford: herramienta de triaje

Abstract: Introducción: Con la escala de Glasgow-Blatchford (EG-B) se califica mediante datos clínicos, el riesgo de resangrado después de hemorragia del tubo digestivo alto (HTDA); y con las escalas de Forrest y Dagradi, mediante endoscopia. Objetivo: Evaluar la capacidad de la EG-B para identificar riesgo de resangrado a 30 días después de una HTDA; el estándar de oro de comparación fue la endoscopia. Método: Se analizaron 129 expedientes de pacientes con HTDA y endoscopia. Se cuantificaron las escalas de Glasgow-Bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
0
1
1
Order By: Relevance
“…
The work carried out by Olivarec et al evaluated the ability of the Glasgow Blatchford score (GBS) to identify the risk of re-bleeding 30 days after upper gastrointestinal bleeding, and it was found to be useful; however, there is literature that contradicts this study. 1 Chang et al, on the contrary, demonstrate the importance of GBS for predicting mortality, need for blood transfusion and the need for endoscopic intervention; however, it is not useful for predicting the risk of re-bleeding, given that, in the study by Olivarec et al, they exclude the presentation characteristic parameter and comorbidities, in contrast to this study. 2 Stanley et al found that the Progetto Nazionale Emorrhagia Digestiva (PNED) score is superior to GBS for re-bleeding, due to the usefulness of re-bleeding and endoscopy within its score; in addition it predicted 7-day re-bleeding; however they conclude that no system predicts re-bleeding risk.
…”
contrasting
confidence: 54%
“…
The work carried out by Olivarec et al evaluated the ability of the Glasgow Blatchford score (GBS) to identify the risk of re-bleeding 30 days after upper gastrointestinal bleeding, and it was found to be useful; however, there is literature that contradicts this study. 1 Chang et al, on the contrary, demonstrate the importance of GBS for predicting mortality, need for blood transfusion and the need for endoscopic intervention; however, it is not useful for predicting the risk of re-bleeding, given that, in the study by Olivarec et al, they exclude the presentation characteristic parameter and comorbidities, in contrast to this study. 2 Stanley et al found that the Progetto Nazionale Emorrhagia Digestiva (PNED) score is superior to GBS for re-bleeding, due to the usefulness of re-bleeding and endoscopy within its score; in addition it predicted 7-day re-bleeding; however they conclude that no system predicts re-bleeding risk.
…”
contrasting
confidence: 54%
“…3 Acadêmico de Medicina-Faculdade Ciências Médicas de Minas Gerais-(FCMMG). 4 Acadêmico de Medicina-Faculdade Ciências Médicas de Minas Gerais (FCMMG). 5 Acadêmico de Medicina-Pontifícia Universidade Católica de Minas Gerais (PUC-MG).…”
unclassified
“…El trabajo realizado por Olivarec, et al evaluó la capacidad de escala de Glasgow Blatchford (GBS) para identificar el riesgo de resangrado a 30 días después de la hemorragia digestiva alta, encontrando que esta es útil; sin embargo, se encuentra bibliografía que contradice este estudio 1 .…”
unclassified